Pengembangan Media Pembelajaran Career Profession Card Untuk Meningkatkan Wawasan Karir Siswa Sekolah Menengah Atas - Rochani Rochani; Bangun Yoga Wibowo; Arga Satrio Prabowo (Universitas Sultan Ageng Tirtayasa, 2020)
Careers that developed throughout human life require academics and researchers to continue program development, methods and media to develop. The development of career maturity that has been underestimated and now, it considered to be important. It indicated by the number of studies related to career development in Indonesia both in terms of programs, methods, and media development. So far, career development media that have been developed sometimes follow the times so that the results are not very effective. This research intends to develop a career development media that can help students improve career insights that affect student career maturity. The media, called the Career Profession Card, will be a solution offered to teachers of guidance and counseling at school in order to help students improve their career insight.